Dataran Maybank / Afiq Eqwan Azman ... [et al.] - Azman, Afiq Eqwan; Abu Bakar, Ahmad Syarifuddin; Abdul Rasid, Ain Nurul Ashikin; Razali, Fathin Nur Amierah; Lukman, Fatin Nabilah; Rosly, Mohammad Qhairul Azhar (2013)
Dataran Maybank is a 39-storey corporate office building situated at Jalan Maarof, Bangsar. This building has three (3) towers. Tower A, B and C. The owner this building is Etiqa Insurance and Takaful Property. Tower A and B rented by Maybank and tower C is belongs to Etiqa Property. This building officially is habited at 2001. This building was officially launched by the former Prime Minister, Tun Abduallah Badawi in 2001. It is located near to Menara UOA Bangsar. Dataran Maybank comprises of 3 towers in which 2 towers comprises of 20-storeys while the third tower comprises of 22-storeys. These 3 towers are the headquarters for Maybank Finance, Maybank Life and Maybank Assurance. Dataran Maybank offers office spaces starting from built-up areas of 1,000 sf and also provides facilities such as 24 hours security, 1,028 covered parking lots and centralized air conditioning, food court with seating capacity of 316, café, product and art gallery, surau, convenience shop and florist, multi-purpose hall, sports recreation room, function room with approximately 200 sf each and sick bays. Dataran Maybank layout has been attributed to the “Family Unity” concept within the Maybank Group. The three towers are enclosed within a circle to emphasize this concept. The building has also been designed with an eco-friendly garden on the podium roof that connects the three towers together. This design stresses the unity amongst the Maybank Group.